2006
DOI: 10.1007/s00134-005-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound estimation of volume of pleural fluid in mechanically ventilated patients

Abstract: Easy quantification of pleural fluid may help to decide about performing thoracentesis in high-risk patients, although thoracentesis under ultrasound guidance appears to be a safe procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
184
1
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(205 citation statements)
references
References 17 publications
(24 reference statements)
0
184
1
15
Order By: Relevance
“…It is measured with the patient in the supine position by moving the probe from the diaphragm upward along the posterior axillary line to design a cross-section perpendicular to the longitudinal axis of the body from the base of the lung, where the separation between the two pleurae is visible. In this study, a significant correlation was found between ''Sep'' and the amount of pleural fluid evacuated at thoracentesis with a success rate of 100 % and a mean prediction error of 158.4 ± 160.6 ml [39]. US can distinguish between transudates (anechoic) and exudates (echoic and loculated) and is also increasingly used to guide bedside thoracentesis and thoracostomy.…”
Section: Hemothoraxmentioning
confidence: 73%
“…It is measured with the patient in the supine position by moving the probe from the diaphragm upward along the posterior axillary line to design a cross-section perpendicular to the longitudinal axis of the body from the base of the lung, where the separation between the two pleurae is visible. In this study, a significant correlation was found between ''Sep'' and the amount of pleural fluid evacuated at thoracentesis with a success rate of 100 % and a mean prediction error of 158.4 ± 160.6 ml [39]. US can distinguish between transudates (anechoic) and exudates (echoic and loculated) and is also increasingly used to guide bedside thoracentesis and thoracostomy.…”
Section: Hemothoraxmentioning
confidence: 73%
“…In this study, an equation was described between the volume of the effusion and the separation distance between the lung and the outer parietal pleura as the effusion size (cc) = 20 × separation (sep) in mm, where the separation (sep) was identified as the maximal separation distance between the parietal and visceral pleura during end-expiration. In this study, a lower frequency probe was used [13].…”
Section: Indications For Chest Ultrasound: Evaluation Of Pleural Effumentioning
confidence: 99%
“…In contrast, the pneumothorax rate associated with ultrasound-guided thoracenteses was lower, ranging from 0 to 9.1%. The rates of subsequent chest tube insertion for pneumothoraces ranged from 2.2-7% in those procedures without ultrasound guidance and 0-3.7% in procedures performed with ultrasound guidance [6,13,22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Overall Incidence Of Pneumothorax and Impact Of Ultrasoundmentioning
confidence: 99%
“…5 On the other hand, sonography has the capacity to clarify the nature of opaque lesions such as effusions, atelectasis, masses and consolidations. 8 Over the years, sonography has been restricted to detection of effusions and procedure guidance (thoracocentesis, biopsy or drainage), 2 providing a high success rate and low morbidity 5 . In recent years, studies have shown that sonography achieves better results than radiography in measuring the effusion volume.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have shown that sonography achieves better results than radiography in measuring the effusion volume. [8][9][10][11] However, the confidence intervals for such measurements remain wide. For this reason, and because of the heterogeneity of the methods proposed in different studies, large-scale use of sonography has been impeded.…”
Section: Introductionmentioning
confidence: 99%